Hubungan Efikasi Diri dengan Kesiapan Kerja Mahasiswa Program Studi Profesi Ners - Ance Siallagan; Vina Sigalingging; Susi Rajagukguk (JINTAN: Jurnal Ilmu Keperawatan, 2022)
Introduction: Work readiness is an advanced condition or process that will be experienced by students after they feel ready and have the knowledge, attitudes, and skills needed by the world of work. Apart from work experience, work readiness is also influenced by individual internal conditions such as maturity and mental readiness and everything that requires their seriousness and focus. Work readiness requires a competency that must be prepared beforehand, this competency is influenced by the existence of self-efficacy. Self-efficacy, also known as social cognitive theory, or social learning theory, refers to an individual's belief that he or she is capable of carrying out a task. Objective: This study aims to determine the relationship between self-efficacy and work readiness of nursing professional study program students at STIKes Santa Elisabeth Medan in 2021. Methode: The research method used is correlation with a cross sectional approach, the number of respondents is 84 people. Sampling technique with total sampling technique. The results obtained were 61 people (72.6%) had high self-efficacy and 63 people (75.0%) student respondents had work readiness in the ready category. Results: The results of the Spearman Rank statistical test obtained a value of r = (.879) and p (value) = 0.000 (p <0,05). Conclusion: There is a significant relationship between self-efficacy and student work readiness. Where the correlation level is in the high category and the direction of the relationship is positive, which means the higher the self-efficacy, the higher the student’s job readiness. Suggestion: Students are expected to be able to maintain or improve self-efficacy and work readiness so that they are able to enter the world of work and carry out tasks or jobs that will be obtained in the world of work.